2002
DOI: 10.1091/mbc.02-05-0064
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Functional Domains of Yeast Sorting Nexins Vps5p and Vps17p

Abstract: Sorting nexins (Snxs) are a recently discovered family of conserved hydrophilic cytoplasmic proteins that have been found associated with membranes of the endocytic system and that are implicated in the trafficking of many endosomal membrane proteins, including the epidermal growth factor receptor and transferrin receptor. Snx proteins are partly defined by the presence of a p40 phox homology domain that has recently been shown to bind phosphatidylinositol 3-phosphate. Most Snx proteins also contain a predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 32 publications
7
103
0
1
Order By: Relevance
“…this reflects characteristics of other parts of these sorting nexins-particularly their coiled-coil regions, which have been shown to drive homo-and hetero-oligomerization in other studies. This finding has been confirmed independently in a study of the Vps17p-Vps5p interaction (31). A notable class of preys consists of the Yip1 family of proteins (32).…”
Section: Resultsmentioning
confidence: 61%
“…this reflects characteristics of other parts of these sorting nexins-particularly their coiled-coil regions, which have been shown to drive homo-and hetero-oligomerization in other studies. This finding has been confirmed independently in a study of the Vps17p-Vps5p interaction (31). A notable class of preys consists of the Yip1 family of proteins (32).…”
Section: Resultsmentioning
confidence: 61%
“…Size fractionation by gel filtration revealed that the amoebic retromerlike complex showed an apparent molecular weight of 300 -500 kDa (unpublished data), which is comparable to that in mammalian cells (Haft et al, 2000). The missing components, sorting nexins and Vps5/17, possess PX domain and BAR domain for the interaction with phosphatidyl inositol 3-phosphate and the curbed membrane (Seaman and Williams, 2002;Habermann, 2004;Seaman, 2005). We found proteins possessing either the BAR domain or the PX domain, but failed to find a protein containing both domains in the genome database.…”
mentioning
confidence: 87%
“…The ability to grow in the absence of histidine (-His) is indicative of interactions. A summary of the results from three independent experiments is presented in Table 1 (a) Lysates from HeLa cells that were either not transfected (lanes 1 and 8, NT) or transfected with cDNAs encoding wild-type (lanes 2 and 9), IM-235,236-DD (lanes 3 and 10), Δ238-246 GG (lanes 4 and 11), 238-246 polyS (lanes 5 and 12), G238P (lanes 6 and 13) and R69A E71A (lanes 7 and 14) forms of myc-tagged Vps26 were subjected to immunoprecipitation (IP) using a mouse monoclonal antibody to the myc epitope The lysates (1% of the total, lanes 1-7) and immunoprecipitates (lanes [8][9][10][11][12][13][14] were subsequently analyzed by SDS-PAGE and immunoblotting (IB) with antibodies to the myc epitope (top panel), Vps35 (middle panel) or Vps29 (bottom panel). (b) The intracellular localization of Vps26-myc and the Vps26-myc mutants indicated in the figure (left column shows Alexa 488 green channel), as well as the colocalization of these constructs with SNX1 (middle column shows Alexa 546, red channel), was examined in fixed/permeabilized cells by indirect immunofluorescence and confocal microscopy.…”
Section: Supplementary Materialsmentioning
confidence: 99%